Implementasi Strategi Media Relations Dinas Sosial Kota Tangerang Selatan dalam Penyebaran Informasi Publik melalui Portal Berita Online - Shela Amelia Akhap; Lilik Sumarni; Nani Nurani Muksin (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study is motivated by the crucial role of government public relations in managing effective communication in the digital era, particularly through cooperation with online media to ensure public information is delivered widely, accurately, and credibly. The research aims to analyze the implementation of media relations strategies carried out by the Public Relations Office of the South Tangerang City Social Service, focusing on three main aspects: managing media relations, developing information dissemination strategies, and building cooperative networks with online media. This study employs a qualitative approach using descriptive methods, with data collected through in-depth interviews and documentation. The theoretical framework is based on Yosal Iriantara’s (2019) media relations strategy, which emphasizes relationship management, communication strategies, and network development. The findings indicate that media relations are implemented through formal and informal communication, openness to media needs, the preparation of informative and community-oriented content, and continuous formal and informal collaboration with online media. Overall, the implementation of media relations strategies contributes to building a positive institutional image and enhancing public trust, although challenges remain, including limited advertorial budgets and human resource constraints.